ETIKA DALAM BERKOMUNIKASI DAN KESEHATAN MENTAL PEMUDA - Elsia Yumar; Risma Lili Yuliarta, Herlin Yunisari Deo, Clara Linderi (Jurnal Komunikasi, 2023)
This research aims to investigate the relationship between ethics in communication and the mental health of young people. The mental health of young individuals is a crucial aspect of their lives, and ethical communication can play a significant role in supporting their mental well-being. The research employs a qualitative approach, collecting data through in-depth interviews, participatory observation, and content analysis of relevant materials. The participants are young individuals aged 18-25 from various social and cultural backgrounds. The results of the study indicate that young people who possess awareness and practice ethical communication tend to have better mental health. Communication that prioritizes honesty, mutual respect, and empathy can form positive interpersonal relationships that support mental well-being. The research also identifies internal and external factors that influence the practice of ethics in youth communication, including values instilled by family, education, and media influence. Understanding these factors can provide additional insights for developing intervention programs or education aimed at enhancing awareness of ethical communication. The findings of this research are expected to contribute to eflorts to improve the mental health of young people through an ethical communication approach. Furthermore, this research can serve as a foundation for further studies in this field and ofler guidance for practitioners, educators, and decision-makers in promoting the mental well-being of young people through ethical communication practices